Achievement First : a high-performing network of charter schools faces political and patron pressures - Ahmed, Fawzia; Elias, Jaan; Oster, Sharon M. ([London] : SAGE, 2016)
For decades, the educational establishment had argued that the persistent achievement gap between the test scores of minority inner-city youths and suburban kids could not be leveled by creating better inner city schools. Poor educational performance, it was asserted, was the result of low socioeconomic status (SES) and until the social and economic conditions of the inner city improved, poor city students would score lower on the standardized tests that determine so many of life's opportunities. At the margin, inner city schools could help a few students gain better opportunities, but for the most part, educational elites believed SES was destiny. This case study discusses this topic.
Originally Published in: Ahmed, F., Elias, J., & Oster, S. (2007). Achievement First: A High-Performing Network of Charter Schools Faces Political and Patron Pressures. 07-021. New Haven, CT: Yale School of Management, Yale University.
Description based on online resource; title from home page (viewed on May 3, 2016).
Keywords: elektronické knihy; electronic books; School management and organization -- Case studies; Charter schools -- Case studies; Nonprofit organizations -- Management -- Case studies; Nonprofit organizations -- Finance -- Case studies